Zinc salts induced ionomeric thermoplastic elastomers based on XNBR and PA12. Issue 2 (22nd January 2020) - Chatterjee, T.; Hait, S.; Bhattacharya, A. B.; Das, A.; Wiessner, S.; Naskar, K.
ABSTRACT: Ionomeric TPEs of XNBR and PA12 have been prepared in presence of various zinc salts such as Zinc oxide (ZnO), Zinc peroxide (ZnO2 ) and combination of (ZnO+ZnO2 ). Curing study of XNBR in presence of ZnO, ZnO2 and (ZnO+ZnO2 ) depicts a significant difference in torque values which suggests the formation of both ionic and covalent linkages for ZnO2 crosslinked XNBR whereas the only ionic crosslink formation takes place for ZnO crosslinked XNBR. Further morphology study by scanning electron microscopy (SEM), atomic force microscopy (AFM), physicomechanical properties, dynamic mechanical thermal analysis (DMTA), rheological study and swelling study also supports the above phenomenon. Graphical Abstract: